Synopsis of the genus Scrophularia (Scrophulariaceae) in Turkey - Uzunhi̇sarcikli M. Erkan; Güner, Ebru Doğan; Eki̇ci̇ Murat (Phytotaxa, 2018)
In this study, the synopsis of the genus Scrophularia in Turkey is presented. As a result of the obtained systematic and floristic findings of the last years, Scrophularia now includes 76 taxa (60 species, 1 subspecies and 15 varieties), of which 37 are endemic to Turkey which suggests an endemism rate of 48%. From the nomenclatural point of view, S. cinerascens is considered a synonym of S. versicolor, and four new lectotypes are designated. Main synonyms, nomenclatural types, ecological data, diagnostic keys and distribution of taxa are also given for each accepted taxon.